STABILISASI DIMENSI KAYU JATI CEPAT TUMBUH DAN JABON DENGAN PERLAKUAN PEMADATAN SECARA KIMIA - Efrida Basri; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 2015)
In general, wood from plantation forests are dimensionally unstable, therefore, timber use are limited. T s his paper observes dimensional stability of chemically densified fast-growing teak (JCT) and jabon woods. JCT and jabon woods were impregnated using a mixture of old teak sawdust extracts and resin. The resin used were vinyl acrylic and polyvinyl acetate in three concentrations : 8, 10, and 12% (w/ v), and two compositions of resorcinol resin. Results show that in general, dimensions of the impregnated wood are more stable than non-impregnated wood. Wood impregnated with the mixture of teak extract solution and resorcinol resin shows better dimentional stability than other resins.